Personality and Emotional Self-efficacy: the Relationship between HEXACO's Emotionality, Extraversion and Conscientiousness with Regulatory Emotional Self-efficacy Belief - Zbigniew Szczepan Formella; Lorenzo Filosa; Giuseppe Crea (The Francis de Sales Scientific Society (TNFS.PL), 2022)
The main objective of this study was to investigate the influences of some personality traits, measured with the HEXACO model of personality, on the perceived ability to manage one's own affects. The results of the correlations and the linear regressions between the personality traits, measured by the HEXACO-60, and the perceived ability to manage affects, measured by the Regulatory Emotional Self-Efficacy Belief scale, support the idea that extraversion is more related to expressing positive affects, whereas emotionality is more related to managing negative affects, and conscientiousness is slightly related to some aspects of self-regulation of positive and negative affects. The results obtained in this study for the HEXACO are similar to those displayed for FFM in previous studies regarding personality traits and positive and negative affects.